A novel reduced graphene oxide/carbon nanotube hollow fiber membrane with high forward osmosis performance - Fan, Xinfei; Liu, Yanming; Quan, Xie (Desalination, 2019)
Forward osmosis (FO)-based water treatment and desalination processes have attracted increasing attention to address the global water crisis, but its practical application is restricted by the lack of FO membranes with high permeability and selectivity. In this work, an all nanocarbon-based FO membrane was successfully fabricated via constructing reduced graphene oxide (RGO) on a carbon nanotube (CNT) hollow fiber substrate via electrophoretic deposition coupling with chemical reduction processes. Due to the ultra-low friction and well-defined interlayer spacing, the RGO active layer provided high water permeability and ion selectivity. Meanwhile, the high porosity and good wettability ensured the CNT hollow fiber substrate with low internal concentration polarization, and thus increasing water flux. During against DI water feed using 0.5 M NaCl draw solution, the prepared RGO/CNT membrane presented an outstanding water flux of 22.6 LMH, which is 3.3 times higher than that of the commercial membrane. Meanwhile, its reverse salt flux was only 1.6 gMH in comparison to 2.2 gMH for the commercial membrane. These results indicate that the all nanocarbon-based membrane is an alternative membrane for providing clean water in the FO process. [Display omitted] •Preparation of all nanocarbon-based hollow fiber membrane•Controllable thickness of reduced graphene oxide active layer•Low internal concentration polarization in high porous and hydrophilic substrate•High water flux and low reverse salt flux during forward osmosis process